2016
DOI: 10.1080/10409289.2016.1170523
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Inferential Thinking in Preschoolers: Effects of Discussion on Children’s Story Comprehension

Abstract: Research Findings: This study examines the effects of low-and highcognitive demand discussion on children's story comprehension and identifies contributions of discussion, initial vocabularies, and parent reading involvement. A total of 70 English learner preschoolers took baseline vocabulary tests in Portuguese and English, were randomly assigned to experimental or control conditions, and were read pairs of books in small groups. In the experimental condition, 1 book per pair was discussed using lowcognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
(133 reference statements)
1
29
0
2
Order By: Relevance
“…Discussion after hearing the story was either literal or inferential, while the control group simply heard each book read. The inferential-only discussion group showed significantly better literal and inferential comprehension of stories, compared to the literal-only discussion and control groups (Collins, 2016).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Discussion after hearing the story was either literal or inferential, while the control group simply heard each book read. The inferential-only discussion group showed significantly better literal and inferential comprehension of stories, compared to the literal-only discussion and control groups (Collins, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…In terms of book sharing interventions, Collins (2016) investigated the effect of discussion after book reading with 70, 4- to 5-year-old typically developing Portuguese-speaking children, who were paired on receptive vocabulary scores. A child from each pair was randomly assigned to either an intervention or control group, both involving repeated reading (in English) of three different books in small groups.…”
Section: Introductionmentioning
confidence: 99%
“…Research has established the benefits of text‐based discussion for comprehension (Nystrand, ). Even among students reading in a second language, cognitively challenging discussion supports inferential thinking (Collins, ).…”
Section: The Importance Of Inferencingmentioning
confidence: 99%
“…Students need comprehension instruction in the early grades (McNamara & Kendeou, ); it helps them understand the ultimate goal of reading as constructing meaning, an important message when students also spend a lot of time developing word‐level skills. After researching discussions with preschool English learners, Collins () concluded that “teachers need not wait to engage young learners in cognitively challenging discussion” (p. 932).…”
Section: The Importance Of Inferencingmentioning
confidence: 99%
“…Αυτό σημαίνει να έχει την ικανότητα σύνδεσης των πληροφοριών που παρέχονται από το κείμενο με πληροφορίες που προέρχονται από γενικότερες γνώσεις του αναγνώστη για την καλύτερη κατανόηση και κριτική προσέγγιση του κειμένου, έτσι ώστε το μήνυμα να κατανοηθεί πλήρως (Αϊδίνης & Δαούλα, 2016). Πρόσφατες έρευνες σε παιδιά προσχολικής ηλικίας καταδεικνύουν τη σημαντική συμβολή του αφηγηματικού πλαισίου της γραμματικής των ιστοριών στην ανάπτυξη της ικανότητας κατανόησης συμπερασμών κατά την ακρόαση ιστοριών (Collins, 2016• Filiatrault-Veilleux, Bouchard, Trudeau, & Desmarais, 2015).…”
Section: παιδική λογοτεχνία αφήγηση διαθεματικές προσεγγίσειςunclassified